Kehidupan Sosial-Ekonomi Masyarakat Transmigrasi di Kelurahan Bangun Jaya Tahun 1986-2012 - Belina Pasriana; Isbandiyah I; Sarkowi Sarkowi (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
This study aims to determine the development of the social and economic life of transmigrant communities in A Widodo village Tugumulyo District in 1980-2017. The method that researchers use is descriptive qualitative method. Data collection techniques in research using interview techniques, observation, and documentation. Technical analysis of data with a step triangulation. Based on the results of research and discussion, it is known that the socio-economic life of the A Widodo village in the Tugumulyo District in 1980-2017 has changed from the beginning of the A Widodo feda in 1937 to the present. This changed can be seen from the field of education. Ranging from opening a business, trading, raising livestock, to fish farming and other, other in the fields of education and economic, also seen in the form of social and religious interactin, where individuals interact with each other and help each other help each other, they repect each other’s religions in the village of A Widodo, namely Islam, Protestantism, Catholic Christianity, Hinduism, they do not mock one another or insult religion. Will determine a person’s social status, the higher the level of education the easier it is to find work and the more respected by the surrounding community.